2020
DOI: 10.3390/f11010070
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Pinus Tabuliformis Stands Have Higher Canopy Transpiration Than Dense Stands Three Decades After Thinning

Abstract: Hydrological effects of forest thinning have been studied at small watershed scales using the paired watershed approach since the 1920s. However, how forest transpiration, a critical component of evapotranspiration, changes decades after thinning is not well understood despite its importance for modifying drought resilience of forest ecosystem under climate change. In a semi-arid mountainous area of northern China, we measured growing season sap flow of Pinus tabuliformis, a widely planted afforestation specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…At the 80-year site, Skubel et al ( 2015 ) found a slight increase in transpiration in remaining trees, despite 2012 being a warm and dry year. Past studies have reported that thinning results in greater availability of soil water to remaining trees, leading to higher transpiration and hence photosynthesis (Bréda et al 1995 ; Reid et al 2006 ; Chen et al 2020a ). This may have been the case in our 80-year-old stand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 80-year site, Skubel et al ( 2015 ) found a slight increase in transpiration in remaining trees, despite 2012 being a warm and dry year. Past studies have reported that thinning results in greater availability of soil water to remaining trees, leading to higher transpiration and hence photosynthesis (Bréda et al 1995 ; Reid et al 2006 ; Chen et al 2020a ). This may have been the case in our 80-year-old stand.…”
Section: Discussionmentioning
confidence: 99%
“…Plantation forests in Eastern North America are managed with the vision to enhance their growth, resilience to stresses, and to maximize their carbon sequestration potential (Meehl et al 2007 ; Sippel et al 2016 ). As heat and drought events are likely to be more frequent in the area, due to the predicted warmer climate in the future (IPCC 2014 ; 2018 ; Niinemets 2010 ; Xu et al 2020 ; Chen et al 2020a ; Fernández-Martínez et al 2020 ), their combined effects especially over multiple years, may have serious implications for net carbon sequestration in temperate conifer forests of Eastern North America. The impact of concurrent and consecutive extreme events should be considered while developing forest management practices for climate resiliency and sustainability with the aim of climate change mitigation by way of greenhouse gas reduction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the slope between m and the reference canopy conductance was significantly lower than 0.6 regardless of soil moisture conditions (Figure 9b). Chen, Zhang, Chen, et al (2020) found that the slope is close to 0.6 in a natural environment, and P. tabulaeformis can be classified as an isohydric tree species (Table 2). Hence, tree water use behaviours need to be confirmed by the dynamics of leaf water potential and stomatal conductance (Klein, 2014; Siddiq et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…In reality, other stand variables, such as rooting depth and canopy resistance, may have a strong effect on local water balance [33]. However, simulating these variables and their interactions with local water balance is a complex task [61,62]. For example, Chen and coauthors [62] report on a case where thinning led to increased transpiration through complex biophysical interactions.…”
Section: Effect Of Optimal Harvesting Decisions On Water Yieldmentioning
confidence: 99%
“…However, simulating these variables and their interactions with local water balance is a complex task [61,62]. For example, Chen and coauthors [62] report on a case where thinning led to increased transpiration through complex biophysical interactions. In this study, as the model only simulated moderate thinning, we do not expect that such effects would have a large impact on the results.…”
Section: Effect Of Optimal Harvesting Decisions On Water Yieldmentioning
confidence: 99%